2020
DOI: 10.21203/rs.3.rs-46035/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Fear and Collectivism Influence Public's Preventive Intention Towards COVID-19 Infection: A Study Based on Big Data from the Social Media

Abstract: Background Despite worldwide calls for precautionary measures to combat COVID-19, the public’s preventive intention still varies significantly among different regions. Exploring the influencing factors of the public’s preventive intention is very important to curtail the spread of COVID-19. Previous studies have found that fear can effectively improve the public’s preventive intention, but they ignore the impact of differences in cultural values. The present study examines the combined effect of fear and coll… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The investigation found a positive and significant influence of fear of COVID-19 on ItSAH (H1 accepted). These results are consistent with the previous studies like Huang et al (2020) and Guan et al (2020) who found the fear of COVID-19 distressed and bring anxiety among the people. Besides, these results are in line with Shah et al (2020) who found fear of COVID-19 as a significant predictor of mast purchase attitudes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The investigation found a positive and significant influence of fear of COVID-19 on ItSAH (H1 accepted). These results are consistent with the previous studies like Huang et al (2020) and Guan et al (2020) who found the fear of COVID-19 distressed and bring anxiety among the people. Besides, these results are in line with Shah et al (2020) who found fear of COVID-19 as a significant predictor of mast purchase attitudes.…”
Section: Discussionsupporting
confidence: 93%
“…Labrague and Santos (2021) statistically found that amplified level of fear of COVID-19 is significantly related to increased organizational distress, decreased job satisfaction and both professional and organizational turnover intentions. In China, Huang et al (2020) completed a province-level investigation. The outcomes of the study revealed a positive effect of both fear and collectivism on people's preventive intention.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially when increased security becomes socially normative, acting in line with group norms and for the safety of others may not feel like losing freedom to the same extent as it would to people in a more individualistic cultural context. Consistent with this possibility, some initial evidence from the COVID-19 pandemic suggests that higher levels of collectivism were related to greater support of restrictive policies (Pei et al, 2020), greater compliance with mask and social distancing mandates (Bazzi et al, 2021;Huang et al, 2020;Lu et al, 2021), lower rates of mental health distress (Germani et al, 2020; though see also Kowal et al, 2020), and lower rates of virus transmission and death (Pei et al, 2020).…”
Section: Cultural Differencesmentioning
confidence: 95%
“…Unsurprisingly, this has focused recently on issues related to COVID-19 and work practices [16]. Analysis of Twitter posts is used commonly to identify public experiences and opinions, including recently on COVID-19 and its impact [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].Medical professionals' opinions about COVID-19 have been studied using social media [32], but no studies to date have examined GP wellbeing using social media monitoring, which is the aim of this study.…”
Section: Introductionmentioning
confidence: 99%